Concurrent ordering and phase transformation in SmCo7 nanograins. Issue 28 (30th June 2015) - Seyring, Martin; Song, Xiaoyan; Zhang, Zhexu; Rettenmayr, Markus
Abstract : The complex concurrent processes of ordering and phase transformation in nanocrystalline SmCo7 are for the first time characterized on the atomic scale revealing the hexagonal Sm2 Co17 superstructure as a precursor of the stable rhombohedral Sm2 Co17 . Abstract : Sm–Co alloys with the stabilized SmCo7 phase are most prominent candidates for advanced high temperature permanent magnets, where the stabilization of the SmCo7 phase can be effectuated by nanostructuring. The complex concurrent processes of ordering and phase transformation in a SmCo7 nanograin are characterized on the atomic scale. For the first time early stages of the phase transformation are made visible by highlighting specific superstructures in single nanograins using Fourier reconstruction of high-resolution transmission electron microscopy images. The superstructures are only detectable and can only be distinguished in specific crystallographic orientations. The evolution of the atom arrangement in the crystal structures is demonstrated for the concurrent ordering process and phase transformation. During decomposition of the metastable SmCo7 phase, the hexagonal Sm2 Co17 superstructure (2:17H) forms at first as a precursor of the rhombohedral Sm2 Co17 superstructure (2:17R) – this can only be detected by analysis of individual grains and has not been described so far. By extensive crystallographic analysis of individual nanograins, a distinct correlation between the fraction of the superstructure phases and the grain size is found, showing directly and unambiguously the grain size dependence of the phase transformation in the nanocrystalline alloy, a phenomenon that so far has only been shown indirectly using volume averaging methods.